Estudo de caracterização dos polimorfismos das regiões promotoras das citocinas fator de necrose tumoral a (TNF-a), interleucina 6(IL-6) e interleucina 10(IL-10) em pacientes com hepatite Delta - Affonso, Juliana dos Santos (2020)
The hepatitis Delta virus is one of the main factors responsible for fulminant hepatitis in cases of acute infection and causes the accelerated progression of liver disease in chronic HBV carriers. The SNPs located in the promoter regions of the TNFɑ -308G/A, IL6 -174G/C and IL10 -1082A/G genes may be related to fibrosis progression, liver cirrhosis, development of CHC and risk of death. Objective: To evaluate the influence of polymorphisms on the genes for Tumor Necrosis Factor alpha (TNF-α), Interleukin 6 (IL-6) and Interleukin 10 (IL-10) genes in patients with Delta Hepatitis. Study design: The study population consisted of seventy-seven (77) patients with hepatitis Delta and one hundred and thirty-seven (137) eligible blood donors who make up the control group. The genomic regions of interest of the IL6, TNFα and IL10 genes were amplified by PCR-RFLP. The measurement of cytokines was performed by flow cytometry. Results: The G/A genotypes (TNFα -308G/A) and G/C (IL6 -174G/C) appear to be risk factors for HDV infection. The analysis of serum cytokine concentrations in the HDV group showed that cytokines IL-2 (p<0.0001), IL-4 (p<0.0001), IL-6 (p<0.0001), IL-10 (p<0.0031) found significantly increased in the HDV group. Serum cytokine levels for individuals in the HDV group IL-6G/C+C/C + IL-10A/G+G/G demonstrated higher levels of cytokines IL-2 (p<0.0066), IL-4 (p<0.0053), IL-6 (p<0.0076), IL-10 (p<0.0309) and IFN-γ (p<0.0199). Conclusion: Our findings demonstrate relevance on the influence of the studied SNPs in patients with HDV on the cytokine profile. TNFɑ -308G/A and IL6 -174G/C may predispose individuals to Hepatitis D infection. The presence of the combined IL-6G / C + CC + IL-10A / G + G / G genotypes alters the profile of the cytokines IL-2, IL-4, IL-6, IL-10 and IFN-γ. However, future studies must be carried out to better elucidate the influence of these SNPs on the pathogenesis of Hepatitis Delta